The Political Economy of Privatization of Education: Role of Local Politicians in India - Muneer Kalliyil; Soham Sahoo (Institute of Labor Economics (IZA), 2024)
We investigate the role of political favouritism in the private education market. Using constituency-level panel data and a close-election regression discontinuity design, we estimate the causal effect of having a politician aligned with the state ruling party on the growth of private educational institutions in India. We find that constituencies represented by aligned politicians have a higher growth rate in the number of private schools, while the effect is insignificant for government schools. Similar patterns are also found for higher education institutions. As potential mechanisms, we explore political influence over bureaucratic processes and discrepancies in the enforcement of government regulations.
Keywords: D72; D73; H11; H75; I25; 330; ruling party alignment; private schools; close elections; regression discontinuity design; India